2021
DOI: 10.1002/aoc.6260
|View full text |Cite
|
Sign up to set email alerts
|

Green and sustainable palladium nanomagnetic catalyst stabilized by glucosamine‐functionalized Fe3O4@SiO2 nanoparticles for Suzuki and Heck reactions

Abstract: A novel magnetic and heterogeneous palladium‐based catalyst stabilized by glucosamine‐functionalized magnetic Fe3O4@SiO2 nanoparticle was synthesized. The strategy relies on the covalently bonding of glucosamine to cyanuric chloride‐functionalized magnetic nanoparticles followed by complexation with palladium. The structure of magnetic nanocatalyst was fully determined by FT‐IR, XRD, DLS, FE‐SEM, TEM, ICP, UV‐Vis, TGA, VSM, and EDX. The obtained results confirmed that the palladium nanoparticles stabilized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 85 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…Evaluation of the sample’s light reflectance activity by UV-DRS could be another helpful method for investigating the presence of the components in the combined solid form . Based on the previous reports, the silica-coated Fe 3 O 4 NPs’ samples could reflect the UV–vis light in a wavelength range of 200–330 nm . Also, the individual VAN shows its major reflectance activity with a sharp peak at 220 nm, and the rest reflectances have appeared as a broad peak enlarged to 350 nm .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Evaluation of the sample’s light reflectance activity by UV-DRS could be another helpful method for investigating the presence of the components in the combined solid form . Based on the previous reports, the silica-coated Fe 3 O 4 NPs’ samples could reflect the UV–vis light in a wavelength range of 200–330 nm . Also, the individual VAN shows its major reflectance activity with a sharp peak at 220 nm, and the rest reflectances have appeared as a broad peak enlarged to 350 nm .…”
Section: Resultsmentioning
confidence: 98%
“…63 Based on the previous reports, the silica-coated Fe 3 O 4 NPs' samples could reflect the UV−vis light in a wavelength range of 200−330 nm. 71 Also, the individual VAN shows its major reflectance activity with a sharp peak at 220 nm, and the rest reflectances have appeared as a broad peak enlarged to 350 nm. 72 Hence, comparing the UV-DRS spectra of the final product and the controls can be informative.…”
Section: Uv−vis Diffuse Reflectance Spectroscopy (Uv-drs)mentioning
confidence: 96%
“…SEM images of the catalyst after the second run revealed the agglomeration of Pd nanoparticles on the surface of the catalyst, which is the major reason for the drop in the product yields as shown in Figure 8. The yield after the second run reaction was still high (>90%) and dropped to 80% after the fifth run but dramatically decreased to 50% after the sixth 1 a CS-NNSB-Pd(II) (0.006) -50 c 0.08 97 Baran [28] 2 ImmPd-MNPs (0.14) TBAB/H 2 O r.t. 0.3 93 Hajipour and Tavangar-Rizi [29] 3 CS-Biguanidine/Pd (0.15) EtOH/H 2 O 40 1 98 Veisi et al [32] 4 Pd@Cell-EDTA (0.05) EtOH/H 2 O 78 0.5 96 Xu et al [11] 5 PdNPs@chitosan (0.1) TBAB 90 5 97 Cotugno et al [17] 6 PdNPs/GO-TETA (0.01) DMF/H 2 O 90 0.4 98 Mirza-Aghayan et al [19] 7 F e 3 O 4 @SiO 2 /PropylSB@Pd (0.1) H 2 O/EtOH 80 c 0.5 92 Hasan et al [6] 8 F e 3 O 4 /CS-Me@Pd (0.003) EtOH/H 2 O 50 30 98 Wang et al [36] 9 Cell-Sc-Pd(II) (0.002) EtOH/H 2 O 70 1.5 74 Pharande et al [12] 10 Fe 3 O 4 -CS@tet-Pd(II) EtOH/H 2 O 90 2.2 91 Nasrollahzadeh et al [40] 11 a Fe 3 O 4 @Guanidine-Pd (0.22) H 2 O 70 0.5 90 Halligudra et al [8] 12 Fe 3 O 4 @SiO 2 -TCT-GA-Pd(0) (0.12) EtOH/H 2 O 50 1.5 95 Eslahi et al [9] 13 PdNPs@CS/δ-FeOOH (0.05) EtOH/H 2 O r.t. 3 91 Çalıs ¸kan and Baran [21] 14 Fe 3 O 4 @MCM41@NHC@Pd (0.01) run. From these results, it can be concluded that the catalyst was effective for five runs.…”
Section: Recycle Of the Catalystmentioning
confidence: 99%
“…[1][2][3] Among the crosscoupling reactions, the Suzuki-Miyaura reaction is one of the powerful tools to create a carbon-carbon bond from the cross-coupling of aryl boronic acid and aryl halides using a palladium catalyst to synthesize biaryls for industrial uses related to pharmaceuticals, agrochemicals, polymers, and materials. [4,5] Recently, many research groups have demonstrated the use of various kinds of materials as catalyst support for the Suzuki-Miyaura reaction, including organic and inorganic compounds such as metal oxides, [6][7][8][9][10] polymers, [11][12][13][14][15][16][17][18] carbon materials, [19,20] and composite materials. [21,22] Among these support materials, natural polymers have attracted much attention due to their availability, nontoxicity, biodegradability, and low cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation